Should patients with acute coronary disease be stratified for management according to their risk? Derivation, external validation and outcomes using the updated GRACE risk score. Issue 2 (21st February 2014) - Fox, Keith A A; FitzGerald, Gordon; Puymirat, Etienne; Huang, Wei; Carruthers, Kathryn; Simon, Tabassome; Coste, Pierre; Monsegu, Jacques; Gabriel Steg, Philippe; Danchin, Nicolas; Anderson, Fred
Abstract : Objectives: Risk scores are recommended in guidelines to facilitate the management of patients who present with acute coronary syndromes (ACS). Internationally, such scores are not systematically used because they are not easy to apply and some risk indicators are not available at first presentation. We aimed to derive and externally validate a more accurate version of the Global Registry of Acute Coronary Events (GRACE) risk score for predicting the risk of death or death/myocardial infarction (MI) both acutely and over the longer term. The risk score was designed to be suitable for acute and emergency clinical settings and usable in electronic devices. Design and setting: The GRACE risk score (2.0) was derived in 32 037 patients from the GRACE registry (14 countries, 94 hospitals) and validated externally in the French registry of Acute ST-elevation and non-ST-elevation MI (FAST-MI) 2005. Participants: Patients presenting with ST-elevation and non-ST elevation ACS and with long-term outcomes. Outcome measures: The GRACE Score (2.0) predicts the risk of short-term and long-term mortality, and death/MI, overall and in hospital survivors. Results: For key independent risk predictors of death (1 year), non-linear associations (vs linear) were found for age (p<0.0005), systolic blood pressure (p<0.0001), pulse (p<0.0001) and creatinine (p<0.0001). By employing non-linear algorithms, there was improved model discrimination, validated externally. Using the FAST-MI 2005 cohort, the c indices for death exceeded 0.82 for the overall population at 1 year and also at 3 years. Discrimination for death or MI was slightly lower than for death alone (c=0.78). Similar results were obtained for hospital survivors, and with substitutions for creatinine and Killip class, the model performed nearly as well. Conclusions: The updated GRACE risk score has better discrimination and is easier to use than the previous score based on linear associations. GRACE Risk (2.0) performed equally well acutely and over the longer term and can be used in a variety of clinical settings to aid management decisions.